EFFECTIVENESS MODEL OF AGRICULTURAL EXTENSION FOR SWEET CORN (Zea Mays Saccharata Sturt) FARMING IN SUBAK KUMPUL, BONA VILLAGE, BLAHBATUH DISTRICT, GIANYAR REGENCY - I Nengah Surata Adnyana (International Conference on Multidisciplinary Research Perspective, 2025)
Corn is a crucial agricultural commodity in Indonesia, playing a strategic role in the national economy. Increased and high-quality corn production can meet food and animal feed needs, as well as increase farmers’ incomes. However, many corn farmers still face various challenges, such as low productivity, a lack of knowledge about production inputs and cultivation technology, and limited access to market information and supporting services such as extension services. Agricultural extension is one way to improve farmers’ skills and knowledge in managing agricultural businesses. However, the effectiveness of agricultural extension services still needs to be improved to achieve agricultural development goals. This study aims to (1) analyze the effectiveness of the availability of sweet corn agricultural production facilities in Subak Kumpul, Bona Village, Blahbatuh District, Gianyar Regency, (2) Analyze the effectiveness of the sweet corn farming subsystem in Subak Kumpul, Bona Village, Blahbatuh District, Gianyar Regency, (3) Develop an effective extension model for sweet corn commodities in Subak Kumpul, Bona Village, Blahbatuh District, Gianyar Regency. The population in this study was 42 people with a sample of 20 farmers. The data were analyzed descriptively, qualitatively and quantitatively. The results of the study indicate that (1) the availability of agricultural production facilities such as corn seeds, fertilizers, pesticides, cultivators, and hand sprayers is generally considered ineffective in the Subak Kumpul, Bona Village, Blahbatuh District, Gianyar Regency; (2) Corn farming subsystems such as land clearing, plowing, liming, furrowing, organic fertilizer application, planting, and maintenance are considered ineffective in the Subak Kumpul, Bona Village, Blahbatuh District, Gianyar Regency; (3) An effective extension model is implemented through improving the provision of production facilities and farming by implementing direct extension methods in the form of field schools for the provision of production facilities, resulting in high productivity, quality, and income, and the ability to compete with other commodities. Suggestions that can be made are: (1) fertilizers and pesticides should be prepared in advance when carrying out corn farming, (2) soil cultivation should be carried out before planting.